2018
DOI: 10.1007/s00784-018-2534-7
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal modulation during chewing performance in occlusal dysesthesia patients: a functional near-infrared spectroscopy study

Abstract: Objectives Neuropsychological associations can be considerable in occlusal dysesthesia (OD) patients who routinely complain of persistent occlusal discomfort, and somatization effects in the superior medial prefrontal cortex and the temporal and parietal regions are also present. However, the relationship between physical activity, i.e., chewing, prefrontal cognitive demand, and psychiatric states in OD patients remains unclear. We investigated this relationship in this study. Materials and methods OD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
8
0
2
Order By: Relevance
“…Narita et al 8 also confirmed strong somatization in patients with symptoms of dysesthesia. The test methods included evaluation of occlusal contacts, masticatory muscles activity, imaging of the prefrontal cortex hemodynamics (used to assess the mental state of patients with mental disorders) and the use of the Symptom Checklist-90-R (SCL-90-R) test.…”
Section: Wynikimentioning
confidence: 84%
See 2 more Smart Citations
“…Narita et al 8 also confirmed strong somatization in patients with symptoms of dysesthesia. The test methods included evaluation of occlusal contacts, masticatory muscles activity, imaging of the prefrontal cortex hemodynamics (used to assess the mental state of patients with mental disorders) and the use of the Symptom Checklist-90-R (SCL-90-R) test.…”
Section: Wynikimentioning
confidence: 84%
“…Znaleziono 43 artyku艂y, z kt贸rych po ocenie tytu艂贸w i streszcze艅 wyodr臋bniono 4 oryginalne prace, spe艂niaj膮ce ustalone kryteria w艂膮czenia. [6][7][8][9] Przegl膮daj膮c pi艣miennictwo wybranych artyku艂贸w zakwalifikowano jeszcze jedn膮 prac臋. 10…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A previous report presented averaged recording data for masticatory muscle activities and fNIRS obtained during both right-and left-side chewing in order to exclude functional laterality (Kamiya et al, 2016), and the present study also averaged the bilateral fNIRS data. Recently, the dissociated prefrontal cortex activities were presented during chewing performance in patients complaining of oral dysesthesia as compared with healthy controls, even though jaw muscle activities were not different between those two groups (Narita et al, 2019).…”
Section: Measuring Fnirs For Prefrontal Cortex Activities During Chewmentioning
confidence: 99%
“…Functional near-infrared spectroscopy has been used to reveal the hemodynamic response to stimulus-induced cortical activation in order to evaluate the neurobiology in exercise and cognition (Bhambhani et al, 2006;Tsujii et al, 2013;Moriya et al, 2016), and chewing cognition was also examined by fNIRS in both young and aged subjects (Hasegawa et al, 2013;Kamiya et al, 2016;Yokoyama et al, 2017) as well as psychiatric patients with persistent occlusal dysesthesia (Narita et al, 2019). fNIRS Abbreviations: AD, anterior digastric; BA, pars triangularis Broca's area; DLPFC, dorsolateral prefrontal cortex; EMG, electromyography; FPA, frontopolar area; fMRI, functional magnetic resonance imaging; fNIRS, functional near-infrared spectroscopy; IPG, inferior prefrontal gyrus; Mm, masseter; OFC, orbitofrontal cortex; Ta, anterior temporal.…”
Section: Introductionmentioning
confidence: 99%